Synthesis of Water Hyacinth/Cassava Starch Composite as An Environmentally Friendly Plastic Solution - Syamsuri, M. Mahfudz Fauzi; Marzuki, Hasan; Setiawan, Dedi Wahyu Ari; Rusmaniar, Rusmaniar; Astika, Tri (Equilibrium Journal of Chemical Engineering, 2023)
Abstract. Conventional plastics made from petroleum polymers were the largest contributor to solid waste on earth. Environmentally friendly bioplastic fabricated by compositing starch and natural fibers were proposed to be a solution to this problem. The purpose of this research was to synthesize bioplastic from water hyacinth fiber composite with cassava starch and test its mechanical properties. Bioplastic fabrication was using melt intercalation method using water hyacinth fibers (WHF) with and without alkali treatment mixed with cassava starch (CS) and glycerol as plasticizer. The resulting bioplastic were characterized with FT-IR and tested for mechanical properties. The mechanical test results showed that water hyacinth fiber alkaline treated/cassava starch (WHF-AT/CS) bioplastic has tensile strength, % elongation, and water absorption values of 1.226 MPa, 3.33%, and 10.26%, respectively. While the bioplastic water hyacinth fiber untreated/cassava starch (WHF-UT/CS) has a tensile strength test value, % elongation, and water absorption of 0.306 MPa, 1.67%, and 11.39, respectively.  Therefore it can be said that WHF-AT/CS bioplastic has better mechanical properties when compared to WHF-UT/CS bioplastic.Keywords:Biocomposite, Bioplastic, Cassava Starch, Water Hyacinth Fiber